Coleoptera aquáticos associados à macrófita Salvinia Séguier, 1754 em ambientes lênticos no Estado de São Paulo - Paula, Márcia Cristina de (2014)
Coleoptera is the largest and most diverse order among the Insecta with approximately 400,000 species, the majority terrest, however about 12 thousand species are aquatic. In order to know the Coleoptera fauna associated with the aquatic macrophytes of the genus Salvinia in lentic environments, this study was conducted in two chapters: the first, Coleoptera associated with Salvinia in four oxbow lakes belonging to two watersheds and the second, the Coleoptera fauna associated with Salvinia auriculata in the dam Beija-Flor. The collects were made monthly over a year in two oxbow lakes to Paranapanema River, in the municipality of Angatuba-SP, in two oxbow lakes to Mogi-Guaçú River and in dam Beija-Flor, in the Ecological Station of Jataí, in the municipality of Luiz Antônio-SP. To collect the macrophytes was used a circular sampler with area 0.07 m² and mesh 0.25 mm aperture. The results indicate that there is greater similarity between the communities of Coleoptera of the lakes that are inserted into the same flood plain and, the connectivity between river and lake is not decisive for the richness and abundance of aquatic Coleoptera fauna. The values of the analysis of the richness and abundance of aquatic Coleoptera typically vary with the species of aquatic macrophytes used by these insects as substrate. The Coleoptera fauna presented several and uniforms during, mainly, the warmer periods of the year. In Brazil, studies on Coleoptera associated with macrophytes in lentic environments is currently scarce, thus, this work contributes to the previous knowledge of the ecology of this fauna in southeastern São Paulo State.